USING LARGE-TONNAGE INDUSTRIAL WASTE TO CREATE BITUMEN COMPOSITES WITH IMPROVED FATIGUE LIFE - I. A. Frolov; U. G. Zvereva; T. V. Dudareva; I. A. Krasotkina; V. G. Nikol'skiy; L. R. Lyusova; Ya. A. Naumova (Тонкие химические технологии, 2018)
With the goal of searching effective methods of industrial wastes recycling, filler systems for bituminous binders in road building have been proposed. For the first time in the world, the product of recycled tire rubbers, which is an active powder of discretely devulcanized type of rubber in addition to waste of sulfur produced in technological processes of oil refining, natural gas, etc., have been tested in order to improve the quality of bitumen binders. The rheological properties and fatigue life of the sulfur-bitumen binder have been investigated according to the linear amplitude sweep test (LAS) by using a Smart Pave dynamic shear rheometer (Physica MCR series, Anton Paar, Austria). A technique for preparing samples of sulfur-containing binders has been developed based on the results of photomicrographs analysis obtained by optical microscopy. It has been done to study their fatigue cracking resistance. The analysis of the influence of sulfur and elastic filler on fatigue life has showed that the rise of the quantity of cycles up to fatigue damage of binder samples by the factor of 3-5 (strain of 5% and 2.5%) is due to crumb rubber concentration. The addition of sulfur to ternary systems bitumen/sulfur/elastic filler enables saving energy resources as a result of the possibility of manufacturing sulfur-extended asphalt at lower temperatures.